α-Bungarotoxin Receptors Contain α7 Subunits in Two Different Disulfide-Bonded Conformations - Rakhilin, Sergey (The Rockefeller University Press, 1999)
Neuronal nicotinic α7 subunits assemble into cell-surface complexes that neither function nor bind α-bungarotoxin when expressed in tsA201 cells. Functional α-bungarotoxin receptors are expressed if the membrane-spanning and cytoplasmic domains of the α7 subunit are replaced by the homologous regions of the serotonin-3 receptor subunit. Bgt-binding surface receptors assembled from chimeric α7/serotonin-3 subunits contain subunits in two different conformations as shown by differences in redox state and other features of the subunits. In contrast, α7 subunit complexes in the same cell line contain subunits in a single conformation. The appearance of a second α7/serotonin-3 subunit conformation coincides with the formation of α-bungarotoxin–binding sites and intrasubunit disulfide bonding, apparently within the α7 domain of the α7/serotonin-3 chimera. In cell lines of neuronal origin that produce functional α7 receptors, α7 subunits undergo a conformational change similar to α7/serotonin-3 subunits. α7 subunits, thus, can fold and assemble by two different pathways. Subunits in a single conformation assemble into nonfunctional receptors, or subunits expressed in specialized cells undergo additional processing to produce functional, α-bungarotoxin–binding receptors with two α7 conformations. Our results suggest that α7 subunit diversity can be achieved postranslationally and is required for functional homomeric receptors.